Different origins and processing methods affect the intrinsic quality of ginger: a novel approach to evaluating ginger quality - Wang, Jie; Liu, Yujie; Zuo, Chijing; Zhang, Jing; Liang, Wanhui; Liu, Yan; Yu, Weidong; Yu, Hao; Peng, Can (Frontiers in Chemistry, 2023)
The present study employed HPLC fingerprint and chemometrics analysis to investigate the effect of the origin and extraction methods on the quality of ginger.The study established fingerprints of ginger extracted using three different methods.Similarity analysis (SA), hierarchical clustering analysis (HCA), and principal component analysis (PCA) were utilized to identify the distinctive constituents and trace the origin of ginger. Furthermore, a straightforward and effective discriminatory method was developed for the quality assessment of ginger. The findings revealed that the quality of ginger was significantly influenced by the source and processing method.We express our utmost gratitude for your kind attention to our manuscript and eagerly await the feedback from the esteemed reviewers. Should you have any queries regarding this paper, please feel free to reach out to me at the following address without any hesitation.Thank you very much for your attention to our paper.